Snhg12 targets miR-199a-5p to regulate osteogenic differentiation of TDSCs via the Fzd4/Wnt/β-catenin pathway - Xinyue Li; Binbin Xu; Zhongjie Wang; Mengyi Li; Hao Wu; Bao Chen (RNA Biology)
Heterotopic ossification (HO) is the formation of bone tissue outside the normal skeletal structure following musculoskeletal injury. Long non-coding RNAs (lncRNAs) play a regulatory role in guiding stem cell differentiation towards osteogenic lineages. Through lncRNA sequencing in this study, we observed an up-regulation of small nucleolar RNA host gene 12 (Snhg12) in HO tissues. The precise function of Snhg12 in the process of tendon stem cells (TDSCs) osteogenic differentiation remains uncertain. Our findings suggest that Snhg12 overexpression exacerbated HO, whereas its suppression ameliorated HO. The lncRNA Snhg12 directly targeted miR-199a-5p to alleviate the suppression of Fzd4 caused by miR-199a-5p. Functionally, experiments conducted in vitro and in vivo demonstrated that HO formation was inhibited by the down-regulation of Fzd4 through the up-regulation of miR-199a-5p. In rescue experiments conducted in vitro, the inhibition of miR-199a-5p or overexpression of Fzd4 reversed the improvement in HO caused by Snhg12 knockdown, and Fzd4 regulated the process of osteogenic differentiation in TDSCs by the Wnt/β-catenin pathway. Taken together, these results demonstrate that Snhg12 modulates HO formation via the Snhg12-miR-199a-5p-Fzd4/Wnt/β-catenin signalling pathway.